Prevalence of self‑harm among lesbian, gay, bisexual, and transgender adolescents: a comparison of personal and social adversity with a heterosexual sample in Ghana - Quarshie, E.N.B.; Waterman, M.G.; House, A.O. (BMC Research Notes, 2020)
Objectives: We sought to estimate the prevalence of self-reported self-harm among adolescents identifying as lesbian, gay, bisexual, and transgender (LGBT) in Ghana, and compare self-reported personal and social adversities related to self-harm in this group to those in a random sample of heterosexual adolescents from the same locality. Results: A total of 444 adolescents aged 13-21 years, comprising 74 LGBT adolescents and 370 heterosexual adolescents, provided data. The lifetime prevalence estimate of self-harm was higher in the LGBT group (47%) than the heterosexual group (23%). The LGBT group reported a higher rate of self-harm during the previous 12 months (45%), compared to the heterosexual group (18%). LGBT adolescents reported more alcohol and substance use and more personal social adversities, including various forms of victimisation, than heterosexual adolescents. They were no more likely to report difficulty in making and keeping friends or schoolwork problems than were heterosexual adolescents.
Research Article
Keywords: Accra; Adolescents; Ghana; LGBT; Self-harm; Sexual minority; Homosexuality; Street-connected adolescents; Sub-Saharan Africa; Suicide